Effect of population aging on pulmonary tuberculosis burden in Zhejiang Province, China: a population-based study - Ling, Yuxiao; Wang, Wei; Chen, Songhua; Zhang, Yu; Wu, Qian; Chen, Xinyi; Liu, Kui; Yang, Ke; Luo, Dan; Li, Yang; Zhou, Yiqing; Chen, Bin; et al. (Frontiers in Public Health, 2025)
BackgroundChina’s aging population poses a growing challenge to disease burden. This study aims to evaluate the impact of population aging on the incidence of pulmonary tuberculosis (PTB) in Zhejiang Province, China.MethodsPTB notified incidence data reported to the National Notifiable Diseases Reporting System from 2005 to 2022 were analyzed. The notified incidence from 2023 to 2035 was estimated using exponential regression models. The decomposition algorithm was applied to decompose and quantify the effects of population aging, population growth, and age-specific incidence on the PTB incidence.ResultsBetween 2005 and 2022, the notified incidence of PTB in Zhejiang Province declined from 93.5 per 100,000 to 33.99 per 100,000. The highest notified incidence was observed in those aged 60 years and older, with the population attributable fraction increasing from 18.76 to 27.92%. During this period, PTB cases decreased by 51.22% compared to 2005, driven by a 23.83% increase due to population growth, a 10.26% increase due to age structure, and an 85.31% decrease due to age-specific incidence. The contribution of age structure to the increase in the number of cases was −1.92, −1.69%, 3.28, and 10.60% in the age groups 0–19, 20–39, 40–59, and ≥60 years, respectively.ConclusionNotified incidence of PTB in Zhejiang Province is expected to decrease. However, this decrease may be affected by demographic changes, particularly in older adults. Thus, strengthening public health measures and policies is crucial to achieving the End TB Strategy goal by 2035, emphasizing the need to enhance PTB screening in older adults.